2023
DOI: 10.3390/ijms24098198
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Acetylcholine Receptor M3 Expression and Survival in Human Colorectal Carcinoma—An Unexpected Correlation to Guide Future Treatment?

Abstract: Muscarinic acetylcholine receptor M3 (M3R) has repeatedly been shown to be prominently expressed in human colorectal cancer (CRC), playing roles in proliferation and cell invasion. Its therapeutic targetability has been suggested in vitro and in animal models. We aimed to investigate the clinical role of MR3 expression in CRC for human survival. Surgical tissue samples from 754 CRC patients were analyzed for high or low immunohistochemical M3R expression on a clinically annotated tissue microarray (TMA). Immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
(108 reference statements)
0
0
0
Order By: Relevance
“…While 3 of the 123 low-expression patients died and 10 survived, at 120 months, 127 high-expression patients died and 1 survived. The CPNE7 high/low expression patient group was classified as TNM stage 0, 1/2, 3 [15]. As a result of comparing the CPNE7 expression level and the survival rate of patients, it was confirmed that the higher the expression of CPNE7, the lower the survival rate of the patients, which was statistically significant.…”
Section: Patient Survival Rate According To Cpne7 Expression In Ffpe ...mentioning
confidence: 75%
“…While 3 of the 123 low-expression patients died and 10 survived, at 120 months, 127 high-expression patients died and 1 survived. The CPNE7 high/low expression patient group was classified as TNM stage 0, 1/2, 3 [15]. As a result of comparing the CPNE7 expression level and the survival rate of patients, it was confirmed that the higher the expression of CPNE7, the lower the survival rate of the patients, which was statistically significant.…”
Section: Patient Survival Rate According To Cpne7 Expression In Ffpe ...mentioning
confidence: 75%
“…Analyzing 754 surgical CRC tissue samples, Lobbes et al demonstrated that high expression of M3R correlated with enhanced survivability, particularly in cases with lower tumor grade and a non-mucinous subtype. This association was linked to a more favorable outcome compared to cases with low M3R expression, where survival significantly decreased and higher tumor grade and mucinous subtype were prevalent [32]. Genomic instability is a hallmark of CRC, and metastatic CRC (mCRC) characterized by deficient mismatch repair (dMMR) and MSI can effectively be treated using immune checkpoint inhibitors (ICI) such as pembrolizumab and nivolumab, approved by both the FDA and EMA [12,33,34].…”
mentioning
confidence: 99%